Study of the morphological patterns and association of Epstein-Barr virus and human herpes virus 8 in acquired immunodeficiency deficiency syndrome-related reactive lymphadenopathy - Gujral S; Gandhi J; Valsangkar S; Shet T; Epari S; Subramanian P (Wolters Kluwer Medknow Publications, 2010)
Aims: Study of the morphological patterns of acquired immunodeficiency syndrome (AIDS)-related lymphadenopathy. Settings and Design: We retrospectively selected cases of AIDS-related benign lymphadenopathy. Cases with lymphomas, frank granulomas and necrosis were excluded. We analyzed different morphological patterns and correlated these with immunophenotypic markers along with viral markers human herpesvirus 8-latency-associated nuclear antigen (HHV8-LANA), and Epstein-Barr virus-encoded ribonucleic acid (EBER) studies via in situ hybridization (EBER-ISH). Materials and Methods: We present the morphological patterns of 13 cases of human immunodeficiency virus (HIV)-reactive lymph nodes and their clinical, hematological, biochemical and radiological parameters with special emphasis on the presence or absence of viral markers, including HHV8 and EBV. Results: Common patterns included follicular hyperplasia only (five cases), mixed pattern of follicular hyperplasia with burnt-out germinal centres (four cases), completely atretic follicle (two cases), folliculolysis (11 cases), dumbbell-shaped follicles (three each), progressive transformation of germinal centers (four cases), T-zone expansion (two cases), Reed Sternberg (RS) cells like immunoblasts (two cases), Castleman′s-like features with lollipop-like follicles (three cases) and a spindle cell prominence (one case). CD8+ T-cells were predominant in 12 cases. CD8+ T-cells were prominent in germinal centers (eight cases). Plasmablasts were seen in four cases within the perigerminal center area. Immunohistochemistry for HHV8, i.e. HHV8-LANA were negative in all cases while EBER was detected in 11 cases in the centrocyte-like B cells. Two cases of multicentric Castleman′s disease expressed EBER; however, they did not express HHV8. Conclusion: The wide spectrum of histological changes in HIV-associated lymphadenopathy requires recognition. The histological changes can mimic those of other infective lymphadenitis, follicular lymphoma, Castleman′s disease, progressive transformation of germinal center, Hodgkin′s disease and spindle cell neoplasms. Presence of EBV is common while HHV8 was not seen.